Analisis Faktor Penyebab Kecelakaan Kerja pada Tenaga Medis di Salah Satu Rumah Sakit Kabupaten Bogor - Yorvan Anandadiva; Euis Nurul Hidayah (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
This study aims to analyze the influence of OHS knowledge, OHS attitude, workload, and work fatigue on the incidence of work accidents in Bogor Regency hospitals. The method used was multiple linear regression, with data collection through questionnaires distributed to doctors and nurses. The results of the analysis showed that OHS knowledge, workload, and work fatigue had a significant influence on occupational accidents, while OHS attitude did not show a significant impact. The significance value in the F test was recorded at 0.000, indicating a strong relationship between the independent variables and occupational accidents. The coefficient of determination (R²) of 0.864 indicates that 86.4% of the variation in work accidents can be explained by these variables. The findings suggest the importance of improving OHS knowledge and managing workload and fatigue to reduce the incidence of occupational accidents in hospitals. The implications of this study can serve as a basis for hospital management in designing more effective safety programs and encouraging a safety culture in the work environment. This study emphasizes the need for more attention to managing workload and fatigue to improve the occupational safety and health of medical personnel.